Deconstructing penguins : parents, kids, and the bond of reading - Goldstone, Lawrence, 1947-; Goldstone, Nancy, 1957- (New York : Ballantine Books, 2005)
"Books are like puzzles. The author's ideas are hidden, and it is up to all of us to figure them out." In this reading companion, the Goldstones--noted parent-child book club experts--encourage grownups and young readers alike to adopt an approach that will unlock the magic and power of reading. With the Goldstones' help, parents can inspire kids' lifelong love of reading by teaching them how to unlock a book's hidden meaning. Featuring fun and incisive discussions of numerous children's classics, this dynamic guide highlights key elements--theme, setting, character, point of view, climax, and conflict--and paves the way for meaningful conversations between parents and children. "Best of all," the Goldstones note, "you don't need an advanced degree in literature or forty hours a week of free time to effectively discuss a book with your child. This isn't Crime and Punishment, it's Charlotte's Web."--Publisher description.
1 Penguins 7, Jets 0: How We Got Started 3 -- 2 Everyone Loves a Mystery: Learning to Be a Book Detective 15 -- 3 The Gift of the Greeks: Protagonist, Antagonist, and the Use of Character 25 -- 4 Location, Location, Location: The Importance of Setting 43 -- 5 Crisis and Conflict: Identifying the Climax 59 -- 6 Putting It Together: What Is the Book Really About? 73 -- 7 Who's Right? Point of View 87 -- 8 Obvious Characters, Contrived Endings, and Convenient Plot Devices: Grading the Author 112 -- 9 Songs Without Music: Poetry 130 -- 10 A Book for Practice 150 -- 11 Another Book for Practice 163 -- 12 One More Book for Practice 175 -- 13 Some (Almost) Final Thoughts 188 -- Appendix I Books for Second and Third Grade 195 -- Appendix II Books for Fourth and Fifth Grade 201.
Keywords: Children -- Books and reading; Children's literature -- Study and teaching (Elementary); Reading -- Parent participation; Book clubs (Discussion groups)